Family Support in Caring for Diabetes Mellitus Family Members with Blood Sugar Level Problems in Karangrejo Village Tulungagung Regency - Farida; Yitno; Poppy Farasari (Universitas STRADA Indonesia, 2024)
Background: Diabetes mellitus (DM) is a chronic disease that requires care from family members. Care for diabetes mellitus clients in the family can be influenced, among other things, by support and participation from other family members so that blood sugar levels canbe controlled. Purpose: The aim of this research is to determine family support in caring for family members with diabetes mellitus with problems with blood sugar levels in Karangrejo Village, Tulungagung Regency. Method: The research design used Correlational Analytics with a cross-sectional approach. The research population was diabetes sufferers in Karangrejo Village, Tulungagung Regency,totaling 92 people and the research sample was diabetes sufferers in Karangrejo Village, Tulungagung Regency with a total of 92 respondents selected using total sampling techniques. The research instrument is a questionnaire and data processing is carried out through editing, coding, scoring, tabulation, while data analysis uses the Spearman rho test. Results: The results of the study showed that the majority of respondents with good family support had normal blood sugar levels, namely 60 respondents (76%), while respondents with less family support had high blood sugar levels, namely 28 people (63%). The statistical test results showed that the ρ value was 0.002 with α 0.05, meaning that there was a relationship between family support in caring for family members suffering from diabetes mellitus in Karangrejo Village, Tulungagung District. Conclusion: Family members need to be aware of and provide support for family members who suffer from diabetes mellitus to reduce blood sugar levels, so that blood sugar levels are controlled.